Biodegradation of Gramineous Lignocellulose by Locusta migratoria manilensis (Orthoptera: Acridoidea) - Zhang, Hongsen; Li, Zhenya; Zhang, Hongfei; Li, Yan; Wang, Fengqin; Xie, Hui; Su, Lijuan; Song, Andong (Frontiers in Bioengineering and Biotechnology, 2022)
To explore an efficient and green pretreatment method is an important prerequisite for the development of biorefinery. It is well known that locusts can degrade gramineous lignocellulose efficiently. Locust can be used as a potential resource for studying plant cell wall degradation, but there are few relative studies about locust so far. Herein, some new discoveries were revealed about elucidating the process of biodegradation of gramineous lignocellulose in Locusta migratoria manilensis. The enzyme activity related to lignocellulose degradation and the content of cellulose, hemicellulose and lignin in different gut segment of locusts fed corn leaves were measured in this study. A series of characterization analyses were conducted on corn leaves and locust feces, which including Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared Spectrum (FTIR), X-ray Diffraction pattern (XRD), Thermogravimetric analysis (TG). These results showed that the highest activities of carboxymethyl cellulase (CMCase), filter paper cellulase (FPA) and xylanase were obtained in foregut of locust, which strongly indicated that the foregut was the main lignocellulose degradation segment in locust; furthermore, the majority of nutritional components were absorbed in midgut of locust. The activity of CMCase was significantly higher than that of xylanase, and Mn peroxidase (MnPase) activity was lowest, which might be due to the basic nutrition of locust was cellulose and hemicellulose not lignin based on the results of FE-SEM, FTIR, XRD and TG. Overall, these results provided a valuable insight into lignocellulosic degradation mechanisms for understanding gramineous plant cell wall deconstruction and its recalcitrance in locust, which could be useful in development of new enzymatic pretreatment processes mimicking the locust digestive system for biochemical conversion of lignocellulosic biomass to fuels and chemicals.